2002
DOI: 10.4141/a01-090
|View full text |Cite
|
Sign up to set email alerts
|

An organic acid blend can modulate swine intestinal fermentation and reduce microbial proteolysis

Abstract: The increased use of slow-release organic acids in swine nutrition has prompted more research to assess their possible role in modulating the intestinal microflora as an alternative to antibiotics. Three diets for growing pigs containing 0 (L-NDF), 100 (M-NDF), and 200 g kg-1 (H-NDF) dried sugar beet pulp (SBP) were pre-digested to simulate ileal digestion, and used as substrate in an in vitro cecal fermentation study. The inoculum was collected from pigs immediately after slaughter. Diets tested were L-NDF, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Indeed CV, CVF and CVDF, having the highest phenol and total acid groups' concentrations, seem to yield the highest reduction of ammonia formation. A similar effect has been observed by citric, fumaric and malic acid blend (Piva et al, 2002). However, these carboxylic acids were found not to stimulate fiber digestion, whereas the SBO isolated from compost matter are capable of stimulating fiber digestion and reduce proteolysis at the same time.…”
Section: Overall Remarks On Sbo Effects and Their Chemical Nature-permentioning
confidence: 48%
See 1 more Smart Citation
“…Indeed CV, CVF and CVDF, having the highest phenol and total acid groups' concentrations, seem to yield the highest reduction of ammonia formation. A similar effect has been observed by citric, fumaric and malic acid blend (Piva et al, 2002). However, these carboxylic acids were found not to stimulate fiber digestion, whereas the SBO isolated from compost matter are capable of stimulating fiber digestion and reduce proteolysis at the same time.…”
Section: Overall Remarks On Sbo Effects and Their Chemical Nature-permentioning
confidence: 48%
“…Samples of fermentation fluid were collected from each vessel 0, 4, 8 and 24 h after incubation for ammonia and VA analysis. Chemical analyses of feed and fermentation liquor were performed as previously described (Piva et al, 2002). a Values are means ± standard deviation calculated over five replicates for each treatment; r 2 = correlation coefficient; V F = maximum volume of gas produced (mL); ÎŒ = maximum rate of gas production (mL h …”
Section: In Vitro Intestinal Fermentationmentioning
confidence: 99%
“…Various feed additives such as organic acids, copper sulphate, zinc oxide, probiotics, prebiotics, and herbs have been studied in newly weaned piglets (Easter 1988;Hill et al 2000;Tsiloyiannis 2001). Partnanen and Morz (1999) and Piva et al (2002) reported that the inclusion of organic acids in the diet can enhance growth performance and modulate intestinal microbiota in pigs. Lactic acid has been reported to reduce gastric pH and delay the multiplication of an enterotoxigenic E. coli (Thomlinson and Lawrence 1981) and to be more effective than other organic acids in improving pig growth performance (Tsiloyiannis et al 2001).…”
mentioning
confidence: 99%
“…The degree of their concentration in the digesta reflects the level of intestinal fermentation (Jensen, 2001;Knarreborg et al, 2001;Piva et al, 2002).…”
Section: Discussionmentioning
confidence: 99%